2019
DOI: 10.18502/jad.v13i3.1537
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Meteorological Factors on Hyalomma Species Composition and Their Host Preference, Seasonal Prevalence and Infection Status to Crimean-Congo Haemorrhagic Fever in Iran

Abstract: Background: The impact of environmental factors and host on Hyalomma spp. community structure and abundance in the main Crimean-Congo haemorrhagic fever (CCHF) foci of Iran is largely unknown. Methods: Biotic and abiotic factors, including host, temperature, humidity, altitude, Köppen-Geiger climate types, sea­son, and precipitation on Hyalomma spp. community structure and abundances in 11 provinces of Iran were investigat­ed. Additionally, the possible infection of ticks with CCHF virus was evaluated us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…In contrast, H. marginatum is able to support very cold temperatures and high humidity [86], so its likelihood of becoming established is higher. References: [11,16,30,32,[34][35][36]49,86,87].…”
Section: Life Cyclementioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, H. marginatum is able to support very cold temperatures and high humidity [86], so its likelihood of becoming established is higher. References: [11,16,30,32,[34][35][36]49,86,87].…”
Section: Life Cyclementioning
confidence: 99%
“…are particularly sensitive to environmental parameters ( Table 5). H. lusitanicum is mainly distributed throughout the hot-summer Mediterranean climate (Csa) [35] whilst H. marginatum prefers hot desert climates (BWh) over hot-summer or warm-summer Mediterranean climates (Csa and Csb), cold desert climates (BWk) or cold semi-arid climates (BSk) [49].…”
Section: Relationships To Climatic Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Intrinsic factors, such as genetics and physiology, as well as behavioral traits, may govern an insect’s ability to acquire, support development, and transmit pathogenic agents. Extrinsic factors include the populations of the host reservoir and their activity patterns, climatic conditions, genetic variability in infectivity of pathogens, and even gut microorganisms [ 62 67 ]. Although blackflies are recognized as one of the most important medical and veterinary groups of arthropods due to their vector competence, there is a little information on their biology and ecology in Iran.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies reported that 46% of hyalomma spp. tick samples gathered in Iran were from desert climate, in Sistan and Baluchistan and Yazd provinces [ 33 ]. The Hyalomma tick is active in Iran from the beginning of spring and continues until the middle of summer [ 23 ].…”
Section: Discussionmentioning
confidence: 99%